2005
DOI: 10.1248/bpb.28.1137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Distribution Patterns for Copper and Zinc in Metallothionein and Superoxide Dismutase in Chronic Liver Diseases and Hepatocellular Carcinoma Using High-Performance Liquid Chromatography (HPLC)

Abstract: Metallothionein (MT) was initially discovered from a horse kidney in 1957 as a protein that contained cadmium. Metallothionein is a heat-stable, metal-binding protein with a molecular weight of 6500 to 7000. 1) A number of physiological and biological roles have been suggested for MT, including detoxification of heavy metals, metabolic regulation of Zinc (Zn) and Copper (Cu) (two trace elements that are essential to the body), and a radical-scavenging action that is closely related to the biological defense me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Metallothionein (MT) plays an important role in detoxifying copper [90]. Studies have also shown that while MT exists mainly as Zn-MT in normal hepatic tissues, the concentration of Cu-MT is significantly higher in HCC, particularly in small HCC [91]. The results from the studies support that copper might play a role in the development of HCC.…”
Section: Discussionmentioning
confidence: 90%
“…Metallothionein (MT) plays an important role in detoxifying copper [90]. Studies have also shown that while MT exists mainly as Zn-MT in normal hepatic tissues, the concentration of Cu-MT is significantly higher in HCC, particularly in small HCC [91]. The results from the studies support that copper might play a role in the development of HCC.…”
Section: Discussionmentioning
confidence: 90%
“…It has also been found that, Zn contents in the tumor and cirrhotic liver tissues were significantly lower than that of the adjacent nontumor "normal" tissues which had again lowered Zn levels than normal tissues (Liaw et al, 1997;Sato et al, 2000;Tashiro et al, 2003). Reports further demonstrated that hepatic Zn levels gradually decreased as the hepatocellular lesions progressed from premalignancy to frank malignancy via the late premalignant phase (Nakayama et al, 2002a,b;Kubo et al, 2005) and studies by Eagon et al (1999) showed that Zn levels temporally decreased in hyperplasic rat liver than that of the normal counterpart. HPLC analysis also revealed that, MT exists as antioxidant Zn-MT in normal hepatic tissues, as Cu, Zn-MT in non-cancerous but diseased hepatic parenchyma, and exclusively as pro-oxidant Cu-MT in the cancerous lesions of the tissue (Kubo et al, 2005) owing to gradual decrease of Zn concentration from normal liverpremalignancy-hepatic neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Reports further demonstrated that hepatic Zn levels gradually decreased as the hepatocellular lesions progressed from premalignancy to frank malignancy via the late premalignant phase (Nakayama et al, 2002a,b;Kubo et al, 2005) and studies by Eagon et al (1999) showed that Zn levels temporally decreased in hyperplasic rat liver than that of the normal counterpart. HPLC analysis also revealed that, MT exists as antioxidant Zn-MT in normal hepatic tissues, as Cu, Zn-MT in non-cancerous but diseased hepatic parenchyma, and exclusively as pro-oxidant Cu-MT in the cancerous lesions of the tissue (Kubo et al, 2005) owing to gradual decrease of Zn concentration from normal liverpremalignancy-hepatic neoplasia. In comparison with NNSP, the Cu-MT was found to be significantly greater in the cancerous tissue than the Cu, Zn-MT which was significantly greater than Zn-MT in diseased NNSP Kubo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Copper MT was slightly increased in the noncancerous liver and extraordinarily increased in HCC. We showed the distribution of copper and zinc, which are bound to MT in various tissues Kubo et al 2005). MT was present in the form of Zn-MT in all normal liver, Zn, Cu-MT was dominantly present in non-cancerous liver parenchyma, and Cu-MT was present mostly in HCC.…”
Section: Radicals On Copper Accumulation In Livermentioning
confidence: 91%